A green and efficient route for P − S − C bond construction using copper ferrite nanoparticles as catalyst: a TD-DFT study. (24th October 2020) - Moghaddam, Firouz Matloubi; Daneshfar, Maryam; Azaryan, Reza
Abstract: Magnetic nanoparticles of CuFe2 O4 were applied as catalyst system for one-pot thiophosphate synthesis via the reaction of aryl sulfonyl chlorides with H -phosphonates under conventional heating conditions. This is an extremely efficient and green method for thiophosphate synthesis under base- and solvent-free conditions. Various thiophosphates were obtained in good to excellent yields under the optimized reaction conditions in a short time. The catalyst can be easily recycled from the reaction by an external magnetic field and reused for the next run. In this study, TD-DFT B3LYP/6-31 + G(d) calculations are in good accord with the experimental results. A comparison between experimental and theoretical UV-vis absorption spectra of the thiophosphate 3k has been carried out; and a small hypsochromic shift (only ∼ 2 nm) was displayed at maximum absorption. The aim of this work is to investigate the best method and basis set for thiophosphate compounds; therefore, predictions for these compounds can be performed in theoretical studies. Graphical Abstract: